Role of English Fluency on Job Seekers’ Perspective in West Jakarta: English - Dwi Puji Hastuti; Rizky Mirani Desi Pratama; Cucu Ika Agustianingrum (Journal of English Development, 2025)
The unemployment rate in DKI Jakarta is still a concern; until now, many graduates from different levels of education have not found work. English fluency also become one of the requirements in looking for a job. The research aims to assess the role of English fluency possessed by job seekers by involving approximately 100 people randomly in the West Jakarta area with three sub-districts that will be used as samples, namely Cengkareng sub-district, Kalideres sub-district, and Kembangan sub-district. The sample is from high school/vocational school graduates and universities. The research uses a quantitative approach by spreading e-questionnaires and observations to job seekers. From job seekers ' perspective, the result on English fluency is that 51% are still at the beginner level, 47% are intermediate, and 2% are advanced. From a job seeker's perspective, beginner-level English skill means using basic expressions for introductions, personal details, and simple interactions and knowing everyday vocabulary and phrases, but it requires communication support. 74% need to upgrade their speaking skills to make English fluency effective for job seekers. The research examines job seekers' English fluency from their perspective.